Valorization of textile waste for removal of Cadmium from contaminated water - Humera Aziz; Munir Ashraf; Muhammad Rizwan; Umair Riaz; Saba Akram; Ali Raza; Jean Wan Hong Yong (Scientific Reports)
Abstract The rapid development in agriculture and industrial sectors has raised some serious global issues like heavy metals pollution of water resources. Cadmium (Cd) is amongst the major water pollutants worldwide. In this study, two novel sorbents were prepared by using post-consumer textile waste (PCTW). The waste denim fabric was recycled with environmentally friendly H2O2 and Ozone through oxidation under alkaline conditions to produce several functional groups at the surface (named as ODF@H202 and ODF@03 respectively) that could trap the heavy metal cations from contaminated water. The functionalized fabric sorbents were characterized by Fourier transform infrared spectroscopy (FT-IR), X-Ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-Ray (EDX) that revealed the presence of carboxylic acid, hydroxyl, and amine functional groups on their surfaces. The sorption isotherm, sorption kinetics and sorption thermodynamics were carried out to unravel the sorption process mechanism. The ODF@H202 sorbent was proved more effective by giving maximum adsorption capacity of (238.09 mg g−1) compared to Ozone treatment (175.44 mg g−1) for Cd2+ and achieved within just 20 min for both sorbents. Pseudo 2nd order and Langmuir models confirmed the chemosorption as dominant mechanism for the monolayer sorption of Cd2+ ions onto ODF@H202 and ODF@03. The sorption thermodynamic revealed the sorption process as endothermic and spontaneous in nature. The results showed that both ODF@H202 and ODF@03 sorbents have an efficient potential for sorbing Cd from contaminated water. Furthermore, both ODF@H202 and ODF@03 sorbents were also tested in a regeneration study to investigate the reuse of these sorbents, and we achieved marvelous results. Both sorbents gave up to 90% of the sorption capacity even after 10 recycles. Conclusively, both sorbents can have their implications for the preparation of filters that can be used for the treatment of wastewater. This study has practical significance by tackling the two environmental problems i.e. heavy metal pollution and denim waste.